The Book of Mormon: a biography - Gutjahr, Paul C. (Lives of great religious books, 2012)
Joseph's gold bible -- Holy writ or humbug? -- Multiplying prophets -- Great Basin saints and the book -- Missionary work and the book -- Scholars and the book -- Illustrating the book -- The book on screen and stage -- Appendix 1. Notable Book of Mormon editions in English -- Appendix 2. Book of Mormon translations